The implementation of community engagement in public service delivery in the uk and policy implication to Vietnam - Oanh, Cao Tu (H. : ĐHQGHN, 2020)
This paper explores how community engagement is implemented by the third sector organisation in public service delivery in the UK. This research applied a case-study approach involving two third sector organisations involved in public service delivery in the UK. The study’s findings revealed community engagement as an important aspect in public service delivery that fosters social cohesion and social capital and thus, the implementation of community engagement needs attention to stakeholders’ interaction, social network, and capability. The results are discussed in relation to the implications for policy, especially in relation to frameworks that can support public value enhancement.